If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + -12 = 0 Reorder the terms: -12 + 2n = 0 Solving -12 + 2n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 2n = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 2n = 0 + 12 2n = 0 + 12 Combine like terms: 0 + 12 = 12 2n = 12 Divide each side by '2'. n = 6 Simplifying n = 6
| y=3(-0.375)+8 | | 3w-2(0.5w+1)=-4(2+w) | | x+9x-20=90 | | 3/8+7/8 | | 5x+3x+8=5 | | 3k+5-3k=8 | | 10=5+.50d | | q=2w+2p | | 175^2-7/15m-3 | | 32+a=0 | | 2x+3(5-x)-12=4(x+2) | | 8c=-8 | | m-6=0 | | -x^2-24-11x=0 | | 10x-8=12x+5 | | 8c=-8c | | 1.4/2 | | 2(n+1/3)=3/2+1+1/2n-1/3 | | 8x^2-4x+8=0 | | 3x/4=5x+1/3 | | -5(6+5x)=-5 | | 3=(t-34)/1.96 | | 8n-2=8 | | 3.2/5+5.5/8 | | X^2+x+1=31 | | 42/5+35/8 | | 1/3(t+9)=14 | | x-8=5(x-4) | | y=2e^3x+5 | | (11/4)+(5/102) | | f(x)=2e^3x+5 | | 0.3+0.4(20)=0.1(x+40) |